Cross‐sectional associations of sex hormones with leucocyte telomere length, a marker of biological age, in a community‐based cohort of older men. (20th January 2019) - Yeap, Bu B.; Hui, Jennie; Knuiman, Matthew W.; Handelsman, David J.; Flicker, Leon; Divitini, Mark L.; Arscott, Gillian M.; McLennan, Susan V.; Twigg, Stephen M.; Almeida, Osvaldo P.; Hankey, Graeme J.; Golledge, Jonathan; et al.
Summary: Context: Telomeres protect chromosomes from damage, and shorter leucocyte telomere length (LTL) is a marker of advancing biological age. The association between testosterone (T) and its bioactive metabolites, dihydrotestosterone (DHT) and oestradiol (E2) with telomere length, particularly in older men, is uncertain. The study aimed to clarify associations of sex hormones with LTL in older men. Participants and methods: We used cross‐sectional data from 2913 men aged 76.7 ± 3.2 years with morning blood samples assayed for T, DHT, E2 (mass spectrometry), and sex hormone‐binding globulin (SHBG, immunoassay), to correlate sex hormones with LTL measured using PCR and expressed as T/S ratio in multivariable linear regression models adjusted for age, cardiometabolic risk factors and cardiovascular disease history. Results: Average difference per decade of age was T −0.46 nmol/L, DHT −0.11 nmol/L, E2 −7.5 pmol/L, SHBG +10.2 nmol/L and LTL (T/S ratio) −0.065. E2 correlated with T/S ratio ( r  = 0.038, P  = 0.039) and SHBG was inversely correlated ( r  = −0.053, P  = 0.004). After multivariable adjustment, E2 was associated with T/S ratio (per 1 SD increase E2: coefficient 0.011, P  = 0.043), T and DHT were not associated. When E2 and SHBG were simultaneously included, E2 remained positively (coefficient 0.014, P  = 0.014) and SHBG inversely (coefficient −0.013, P  = 0.037) associated with T/S ratio. Conclusions: In older men, neither T nor DHT is associated with LTL while E2 is independently associated with LTL and SHBG is inversely associated, thus relating sex hormone exposure to lower biological age. Further research is needed to determine causality and clarify the role of sex hormones in male ageing.